Safety and Feasibility for Pediatric Cardiac Regeneration Using Epicardial Delivery of Autologous Umbilical Cord Blood‐Derived Mononuclear Cells Established in a Porcine Model System. (5th January 2015) - Cantero Peral, Susana; Burkhart, Harold M.; Oommen, Saji; Yamada, Satsuki; Nyberg, Scott L.; Li, Xing; O'Leary, Patrick W.; Terzic, Andre; Cannon, Bryan C.; Nelson, Timothy J.
Abstract : This study established a porcine pipeline to evaluate the feasibility and long‐term safety of autologous umbilical cord blood mononuclear cells (UCB‐MNCs) transplanted into the right ventricle (RV) of juvenile porcine hearts. The results show that autologous UCB‐MNCs can be safely collected and surgically delivered in a pediatric setting, establishing the foundation for cell‐based therapy directed at the RV of juvenile hearts and aims to accelerate cell‐based therapies toward clinical trials for congenital heart disease. Abstract : Congenital heart diseases (CHDs) requiring surgical palliation mandate new treatment strategies to optimize long‐term outcomes. Despite the mounting evidence of cardiac regeneration, there are no long‐term safety studies of autologous cell‐based transplantation in the pediatric setting. We aimed to establish a porcine pipeline to evaluate the feasibility and long‐term safety of autologous umbilical cord blood mononuclear cells (UCB‐MNCs) transplanted into the right ventricle (RV) of juvenile porcine hearts. Piglets were born by caesarean section to enable UCB collection. Upon meeting release criteria, 12 animals were randomized in a double‐blinded fashion prior to surgical delivery of test article ( n = 6) or placebo ( n = 6). The UCB‐MNC (3 × 10 6 cells per kilogram) or control (dimethyl sulfoxide, 10%) products were injected intramyocardially into the RV under direct visualization. The cohorts were monitored for 3 months after product delivery with assessments of cardiac performance, rhythm, and serial cardiac biochemical markers, followed by terminal necropsy. No mortalities were associated with intramyocardial delivery of UCB‐MNCs or placebo. Two animals from the placebo group developed local skin infection after surgery that responded to antibiotic treatment. Electrophysiological assessments revealed no arrhythmias in either group throughout the 3‐month study. Two animals in the cell‐therapy group had transient, subclinical dysrhythmia in the perioperative period, likely because of an exaggerated response to anesthesia. Overall, this study demonstrated that autologous UCB‐MNCs can be safely collected and surgically delivered in a pediatric setting. The safety profile establishes the foundation for cell‐based therapy directed at the RV of juvenile hearts and aims to accelerate cell‐based therapies toward clinical trials for CHD.